The Relationship between Lecturer Performance Factors and Increased Insight, Strategy, and Impact on Higher Education Students - Sulistiarini, Emma Budi (Jurnal Pedagogi dan Pembelajaran, 2024)
There are many problems faced by lecturers in higher education in achieving optimal job satisfaction. This is urgent to research because there is a difference between expectations and reality in the work environment of university lecturers. The aim of this research is to analyze factors that influence the level of job satisfaction of lecturers in higher education, with special emphasis on remuneration, duties, and how the work environment. The research method used was quantitative involving 127 randomly selected higher education lecturers. The data collection technique uses a questionnaire whose validity has been tested through a pilot study of 55 respondents. The data collected was then analyzed using SPSS Version 26.0 using the t-test and ANOVA to determine significant differences in job satisfaction levels based on certain factors such as gender, teaching experience, and highest qualifications. As a result, it was found that there were no significant differences in the level of job satisfaction based on remuneration, duties, and work environment factors based on gender, teaching experience, and qualifications in higher education. The conclusion is that certain factors such as remuneration, duties, and work environment do not have a significant effect on the level of lecturer job satisfaction. A practical implication of these findings is the importance of paying attention to other factors contributing to special education faculty job satisfaction and developing strategies to enhance their well-being in supporting students.